Financial integration and the co-movement of economic activity: Evidence from U.S. states - Martin Götz; Juan Carlos Gozzi (Deutsche Bundesbank, 2021)
We analyze the effect of the geographic expansion of banks across U.S. states on the co-movement of economic activity between states. Exploiting the removal of interstate banking restrictions to construct time-varying instrumental variables at the state-pair level, we find that bilateral banking integration increases output co-movement between states. The effect of financial integration depends on the nature of the idiosyncratic shocks faced by states and is stronger for financially dependent industries. Finally, we show that integration increases the similarity of bank lending fluctuations between states and contributes to the transmission of deposit shocks across states.
Keywords: E32; F36; F44; G21; 330; banking integration; synchronization; financial deregulation; business cycles